EXCLUSIVE BREASTFEEDING EDUCATION FOR POSTPARTUM MOTHERS IN THE TANGERANG CITY HOSPITAL: PEMBERIAN EDUKASI ASI EKSKLUSIF KEPADA IBU MELAHIRKAN DI RSUD KOTA TANGERANG - Devia Nurdiyanti; Febi Ratna Sari; Yuli Safitri; Dea Ananda; Elfiana Yusronah; Muhammad Fajri; Nopela (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Breast milk is an important food for newborns. Exclusive breastfeeding can reduce the risk of diarrhea, the risk of pneumonia, and can provide immunity for babies. Objective: This activity aims to increase the knowledge and skills of postpartum mothers regarding how to breastfeed their newborns. Method: This activity started with education, then practicing latching on to the baby’s mouth. Participants in this activity were postpartum mothers at Tangerang City Hospital. Participants were given a pre-test and post-test, discussion, and were given the opportunity to practice giving exclusive breastfeeding directly to their babies. Results: There was an increase in mothers' knowledge regarding exclusive breastfeeding, from 20% to 100%. All participants actively participated in discussions during counseling and practice demonstrations on how to latch on to a baby's mouth correctly. Conclusion: Education can increase mothers' knowledge about exclusive breastfeeding and practice how breastfeed correctly can help mothers undergo exclusive breastfeeding